Cerebellar development after preterm birth - Iskusnykh, Igor Y.; Chizhikov, Victor V. (Frontiers in Cell and Developmental Biology, 2022)
Preterm birth and its complications and the associated adverse factors, including brain hemorrhage, inflammation, and the side effects of medical treatments, are the leading causes of neurodevelopmental disability. Growing evidence suggests that preterm birth affects the cerebellum, which is the brain region involved in motor coordination, cognition, learning, memory, and social communication. The cerebellum is particularly vulnerable to the adverse effects of preterm birth because key cerebellar developmental processes, including the proliferation of neural progenitors, and differentiation and migration of neurons, occur in the third trimester of a human pregnancy. This review discusses the negative impacts of preterm birth and its associated factors on cerebellar development, focusing on the cellular and molecular mechanisms that mediate cerebellar pathology. A better understanding of the cerebellar developmental mechanisms affected by preterm birth is necessary for developing novel treatment and neuroprotective strategies to ameliorate the cognitive, behavioral, and motor deficits experienced by preterm subjects.